2015
DOI: 10.1136/bmj.h102
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide, metformin, and insulin for the treatment of gestational diabetes: a systematic review and meta-analysis

Abstract: At short term, in women with gestational diabetes requiring drug treatment, glibenclamide is clearly inferior to both insulin and metformin, while metformin (plus insulin when required) performs slightly better than insulin. According to these results, glibenclamide should not be used for the treatment of women with gestational diabetes if insulin or metformin is available.Systematic review registration NCT01998113.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

26
322
4
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 383 publications
(381 citation statements)
references
References 34 publications
26
322
4
14
Order By: Relevance
“…This metaanalysis included six randomized trials comparing metformin and insulin. 23 Failure rate of glyburide in our study (2.77%) is also comparable to studies comparing glyburide and insulin. The meta-analysis published in 2015, Odiba et al found the average failure rate of glyburide 6.47% when glyburide was used for the management of GDM.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This metaanalysis included six randomized trials comparing metformin and insulin. 23 Failure rate of glyburide in our study (2.77%) is also comparable to studies comparing glyburide and insulin. The meta-analysis published in 2015, Odiba et al found the average failure rate of glyburide 6.47% when glyburide was used for the management of GDM.…”
supporting
confidence: 86%
“…In another article published in 2015; Odiba et al compared glyburide and insulin for perinatal outcomes and found that treatment of gestational diabetes with glyburide is associated with 1.40 times increased risk of neonatal hypoglycemia and 1.41 times increased risk of having LGA. 23,25 The study was started with null hypothesis. According to that it was presumed that metformin and glyburide are equally effective in achieving glycemic targets without affecting maternal, fetal or neonatal outcomes.…”
mentioning
confidence: 99%
“…An additional study in 2073 women also found higher odds of neonatal intensive care admission (adjusted odds ratio 1.46, 95%CI 1.07–2.00) and birth weight >4000 g (adjusted odds ratio 1.29, 95% CI 1.03–1.64) amongst infants born to mothers receiving glibenclamide during pregnancy 27. The evidence now indicates that glibenclamide treatment in the third trimester exacerbates fetal hyperinsulinism in utero and has an additive effect on birth weight 10, 26, 28. These studies have raised concern regarding the use of glibenclamide in pregnancy 25.…”
Section: Sulfonylurea Treatment In Pregnancy In Type 2 Diabetes and Gmentioning
confidence: 99%
“…Even though good glycaemic control may be maintained, pregnant women with GDM treated with glibenclamide had larger babies than insulin‐treated mothers, further increasing the risk of obstetric and neonatal complications from macrosomia 25, 26. In a meta‐analysis of randomized controlled trials, glibenclamide use resulted in greater birth weight (mean difference 109 g; 95% CI 36–181), and higher risks of macrosomia [risk ratio (RR) 2.62, 95% CI 1.35–5.08) and fetal hypoglycaemia (RR 2.04, 95% CI 1.30–3.20) 10. In a large cohort study from the USA in 110 000 women with GDM, newborns of women treated with glibenclamide (glyburide) were at higher risk of neonatal intensive care unit admission (RR 1.41; 95% CI 1.23–1.62), respiratory distress (RR 1.63; 95% CI 1.23–2.15), hypoglycaemia (RR 1.40; 95% CI 1.00–1.95), birth injury (RR 1.35; 95% CI 1.00–1.82), and large for gestational age (RR 1.43, 95% CI 1.16–1.76) compared with those treated with insulin 26.…”
Section: Sulfonylurea Treatment In Pregnancy In Type 2 Diabetes and Gmentioning
confidence: 99%
See 1 more Smart Citation